Increased circulating nerve growth factor is directly correlated with disease activity in juvenile chronic arthritis. Issue 10 (October 1996) - Falcini, F; Matucci Cerinic, M; Lombardi, A; Generini, S; Pignone, A; Tirassa, P; Ermini, M; Lepore, L; Partsch, G; Aloe, L
Abstract : OBJECTIVE: To determine the circulating serum concentrations of nerve growth factor (NGF) and compare them with indices of disease activity in juvenile chronic arthritis. METHODS: NGF concentrations were evaluated with a two site immunoenzymatic assay (ELISA), in 17 children with systemic, 39 with polyarticular, and 24 with pauciarticular onset juvenile chronic arthritis. Each subset was divided according to different variables, appropriate to each subset, reflecting active and inactive disease. RESULTS: NGF concentrations were significantly higher in children with systemic [254 (SD 256.1) pg ml-1; P < 0.001], polyarticular [165.2 (300.8) pg ml-1; P < 0.05], and pauciarticular [106.8 (111.8) pg ml-1; P < 0.005] onset juvenile chronic arthritis than in controls. In all subsets, NGF concentrations were higher in the active than in the inactive phase of the disease. A significant direct correlation between NGF concentrations and erythrocyte sedimentation rate was found both in the systemic and in the polyarticular onset juvenile chronic arthritis. CONCLUSIONS: The increase in NGF concentrations in all juvenile chronic arthritis subsets and the correlation with disease activity suggest that NGF may take an active part in joint inflammation.